Optical Investigations on In0.11Ga0.89N based LEDs Grown on Si (111) Substrate with Different Superlattices Stack Layer Structure - Azimah, E.; Zainal, N.; Shuhaimi, A.; Egawa, T.; Akimov, A. V.; Kent, A. J. (2015)
Growing lnxGa1-xN based LEOs on Si is considered challenging as the large lattice mismatch between nitrides and Si material would lead to cracks and defects in the nitride layers. This reduces the luminescence efficiency of the devices. Therefore, in this work, we investigate the effect of the inserting different intermediate structure as an effort to reduce the defects from propagating into the multi-quantum wells (MQWs). Here, In0.11Ga0.89N based LEOs grown on Si (111) substrate with AIN/GaN SLS. In between the LEOs and the SLS, intermediate layers were grown in different structure and in different devices. The idea is to further minimize the impact of the defects propagation of defects and cracks into the MOWs region. We found the lno_,,Gao.asN based LEDs with the insertion of AIGaN/GaN SLS exhibits the best internal quantum efficiency than other devices.